Provision of a Medicines Information Service to Consumers on Facebook: An Australian Case Study - Benetoli, Arcelio; Chen, Timothy F; Spagnardi, Sarah; Beer, Troy; Aslani, Parisa (JMIR Publications, 2015)
BackgroundSocial networking sites (SNSs) have changed the way people communicate. They may also change the way people seek health advice. ObjectiveThis study describes the provision of a medicines information service on Facebook to individual consumers. It aimed to discuss the pros and cons, and inform health and pharmacy stakeholders and researchers about the opportunities and challenges of providing such a service. MethodsWe adopted an exploratory approach using a case study method. ResultsNPS MedicineWise, an independent, not-for-profit Australian organization, runs a public question-and-answer service on Facebook, dubbed Pharmacist Hour. Consumers following the organization's Facebook page are invited to post medication-related questions often with a suggested health topic. A wide range of questions and comments are posted related to medication usage. The pharmacist answers the queries, providing evidence-based medicines information and using consumer-friendly language, during the specific 1-hour period. The most popular questions in the past 12 months were related to adverse effects, treatment options for conditions, and drug interactions. The service had a mean number of engagements (defined as a like or share of the Pharmacy Hour post) of 38 (SD 19) people and a mean 5 (SD 3) questions per session. ConclusionsThe Pharmacist Hour Facebook service addresses the medicines information needs of consumers and indirectly promotes other appropriate and relevant NPS MedicineWise products and services to further assist consumers. The service offers a new medium for a quality use of medicines organization committed to promoting awareness about the correct and safe use of medicines in Australia.